PERBAIKAN PROSES PEMISAHAN PENGOTOR PADATAN UNTUK MENINGKATKAN KUALITAS GULA MERAH TEBU RAKYAT DI ACEH TENGAH (Modification of Solid Impurities Removal Process to Improve Brown Cane Sugar Quality Traditionally Produced in Aceh Tengah) - Marwan, Marwan; Indarti, Eti; Abubakar, Yusya; Arpi, Normalina (Jurnal Hasil Penelitian Industri, 2014)
Brown cane sugar is traditionally produced by small enterprises at DesaBlang Mancung (Ketol District, Aceh Tengah Regency), one of them is Sara Ate Enterpriserun by a group of local young men since 2010. The product is purchased by food industriesin Medan and used as ingredients. However, its price was rather low around Rp. 5000,-per kilogram due to high content solid impurities. In this work, we introduced an improveddesign of solid separation equiment to remove un-dissolved content of the brown canesugar juice. A two stage stainless steel screen was applied to filter solids from the juice.The screen also separated entrained bagasse. The filtrate was then flowed to a settler thatallows further separation of solids such as sand or clay. To minimize possibility ofimpurities entrainment during cooking process, the furnace was also modified by usingconcrete construction. As the result, much better brown cane sugar was produced withmuch lower solid impurities (2.2% w/w) and brighter appearance, thus complying grade IISNI 01-6237-2000 .